Effects of suspension and steering parameters on handling of a light commercial vehicle - Acar, Artuğ. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The influence of suspension and steering geometry parameters on lateral drift of a light commercial vehicle is investigated by using Automatic Dynamic Analysis of Mechanical Systems (ADAMS). The aim of this study is to order the effect of suspension parameters on lateral drift. The vehicle that is used in this study is produced in Turkey and is widely used as a light commercial vehicle. Front and rear suspension parameters of the vehicle such as toe, camber and caster are modified in a range in ADAMS/Chassis to calculate their effect on lateral drift. Road tests are done using a real vehicle to compare road test results to computational ones. The effect of suspension parameters on lateral drift of the vehicle are measured to decide which parameters dominate lateral displacement under suitable road conditions without any external input such as wind or unsteady road crown. The suspension parameters that dominate lateral drift of the vehicle the most are determined using a DOE analysis. As a result of statistical analysis, front toe, front caster and rear toe are together dominant parameters that affect lateral drift of the vehicle. The third important parameter group includes front camber and rear toe. It has only two parameters to be equally aligned for the left and right handsides. So, in the assembly of this vehicle front camber and rear toe angles should be perfectly aligned to overcome lateral drift problem.
Keywords: Automobiles -- Springs and suspension -- Design and construction.; Automobiles -- Steering-gear -- Design and construction.; Automobile mechanics.